Biomechanical Consequences of Meniscal Tear, Partial Meniscectomy, and Meniscal Repair in the Knee. Issue 4 (April 2018) - Lau, Brian C.; Conway, Devin; Mulvihill, Jeffrey; Zhang, Alan L.; Feeley, Brian T.
Abstract : Update: This article was updated on April 26, 2018, because of a previous error. On pages 1 and 14, the author name that had read "Alan Z. Zhang, MD" now reads "Alan L. Zhang, MD." Meniscal tears are one of the most common injuries encountered by orthopaedists, and arthroscopic partial meniscectomies and repairs are among the most common procedures performed for their treatment. An understanding of the biomechanical consequences in the knee is needed by treating clinicians. Knee adduction moment is increased following meniscal tears and is further increased following arthroscopic partial meniscectomy. Increased knee adduction moment is associated with the development of tibiofemoral osteoarthritis. Meniscal tears increase contact pressures within the knee when they involve >60% of the width of the meniscus. Partial meniscectomy further increases contact pressures, and meniscal repair partially reduces contact pressures but not to normal levels. Patients may benefit from a focus on rehabilitation following arthroscopic partial meniscectomy to restore proper knee mechanics. In both the medial and the lateral meniscus, repair of radial tears yields better contact biomechanics than resection does. However, resection of up to 50% of the meniscal depth may be acceptable when repair is not feasible. Horizontal cleavage tears of the medial meniscus should be treated with resection of 1 leaflet rather than both when possible.